Non‐Endocardial Radiofrequency Ablation of Premature Ventricular Complexes (NERA‐PVC): Safety, Efficacy and Outcome. - Falzone, Pasquale Valerio; Vazquez‐Calvo, Sara; Guichard, Jean Baptiste; Althoff, Till; Garre, Paz; Tolosana, Jose Maria; Guasch, Eduard; Borras, Roger; Mont, Lluis; Porta‐Sanchez, Andreu; Roca‐Luque, Ivo (Journal of Cardiovascular Electrophysiology, 2025)
Background: Radiofrequency (RF) ablation of premature ventricular complexes (PVCs) is a well‐established treatment for patients high PVCs burden, even when arising from epicardial/intramural localization. Consistent data about safety of using high power RF is lacking in the literature in these regions. Aim: The aim of this study is to investigate the safety of different RF power settings, efficacy and outcome of non‐endocardial PVCs ablation. Methods: Consecutive patients who underwent PVC ablation were included (2017–2023). We defined "Non‐Endocardial Radiofrequency Ablation"(NERA) a procedure in which at least one ablation site has been identified into the CVS, aortic cusps, inter‐leaflet region or pulmonary cusps. Results: Total number of NERA sites was 64 in 56 procedures. In 63% of the procedures, high power (≥ 40 W) and in 60% long duration (≥ 60 s) RF was delivered in at least one site (median power: 40 W(30–40), median duration of single RF 54 s(45–91). In 21% of the procedures, a combination of both high power and long duration RF applications was performed. Overall procedural success was achieved in 46 procedures 82%), complete in 39 (70%), partial in 7 (12%). Only one severe complication (pericardial bleeding) was observed. Multisite ablation was associated with procedural failure. During follow‐up, median PVC burden was 0.5%(0.5–9.5), with a median reduction of 97%. Multisite ablation and coronary venous system RF were predictors of recurrence (HR 3.6; p = 0.03) and HR 3.85; p = 0.02). Conclusion: Ablation from non‐endocardial sites is a safe and effective procedure, even using high power and/or long duration RF with clear benefit in terms of PVC burden reduction.